2016
DOI: 10.1099/ijsem.0.000895
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia minasensis sp. nov., isolated from the tick Rhipicephalus microplus

Abstract: Recently, we obtained a rickettsial isolate (Ehrlichia sp. UFMG-EV T ) from the haemolymph of engorged Rhipicephalus microplus tick females. On the basis of maximum-likelihood phylogenetic analysis using 16S rRNA gene, groEL, dsb, gltA and trp36 sequences we showed that Ehrlichia sp. UFMG-EV T belongs to the a-Proteobacteria, family Anaplasmataceae, genusEhrlichia. Ehrlichia sp. UFMG-EV T is a sister taxon of Ehrlichia canis with 16S rRNA gene, groEL, dsb, gltA and trp36 sequence similarities of 98.3 %, 97.2 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 21 publications
(15 reference statements)
4
63
0
1
Order By: Relevance
“…Ehrlichia genotypes closely related to E. canis have already been detected in wild carnivores , wild birds and domestic cats (André et al, 2015) in Brazil, and rodents in Korea (Kim et al, 2006). In addition, Ehrlichia minasensis, a species closely related to Ehrlichia canis that has been identified infecting Rhipicephalus microplus ticks and cattle in Brazil (Carvalho et al, 2016;Cabezas-Cruz, et al;2016), also showed phylogenetic relatedness with the sequences obtained in the present study, but lower when compared to Ehrlichia canis. Following the same pattern observed with Anaplasma genotypes detected in the present study, the positive samples at cPCR and qPCR assays for Ehrlichia spp.…”
Section: Discussionsupporting
confidence: 61%
“…Ehrlichia genotypes closely related to E. canis have already been detected in wild carnivores , wild birds and domestic cats (André et al, 2015) in Brazil, and rodents in Korea (Kim et al, 2006). In addition, Ehrlichia minasensis, a species closely related to Ehrlichia canis that has been identified infecting Rhipicephalus microplus ticks and cattle in Brazil (Carvalho et al, 2016;Cabezas-Cruz, et al;2016), also showed phylogenetic relatedness with the sequences obtained in the present study, but lower when compared to Ehrlichia canis. Following the same pattern observed with Anaplasma genotypes detected in the present study, the positive samples at cPCR and qPCR assays for Ehrlichia spp.…”
Section: Discussionsupporting
confidence: 61%
“…canis TWN (98.3% and 97.2% respectively) (Cabezas‐Cruz et al . ). Phylogenetic analyses proved that our Corsican strain was most closely related with E .…”
Section: Resultsmentioning
confidence: 97%
“…microplus female tick (Cabezas‐Cruz et al . ). Ehrlichia minasensis was established as a new species in 2016.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Pritt et al (2011) identified a third species of Ehrlichia muris in patients who had fever, malaise, headache, and lymphopenia in Wisconsin and Minnesota, the United States, and it has also been found in Europe and Asia (Rar et al, 2010; Tateno et al, 2015). Other species that infect animals include A. marginale , Anaplasma centrale , A. ovis , E. canis , and Ehrlichia minasensis (Wen et al, 2003; Kocan et al, 2015; Cabezas-Cruz et al, 2016). Several species have been described in China, such as A. ovis , Anaplasma bovis , and A. platys in Gansu province (Li et al, 2016), A. centrale and E. canis in Fujian province (Ge et al, 2016; Yu et al, 2016), and E. chaffeensis in Guangxi province (Yang et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%